Trade flows in developing countries: what is the role of trade finance? - Clara Brandi; Birgit Schmitz (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The availability of trade finance can be an important driver for international trade. This paper analyses the effect of trade finance on the trade flows of industrialized, emerging and developing economies and focuses in particular on the role of trade openness. We use Berne Union data on export credit insurance, the most extensive dataset on trade finance currently available, for the period 2005-2013.Using a two-stage instrumentation approach, we find a significantly positive effect of the availability of trade finance on trade. A one per cent increase in commitments is followed by a 0.27-0.54 per cent increase in total imports in the next year. This is a rather large effect and underlines the importance of trade financing for the smooth exchange of goods across countries and regions. Moreover, we find that trade openness is a very important determinant, not only of import flows but also of how trade credit insurance impacts on trade flows. The more open a country is to trade, the less important is the trade credit insurance effect on imports; when a country is more open to trade, the more frequent exchanges of goods support reliable importerexporter relationships, so that trade partners do not have to rely as much on trade finance instruments. We further investigate how the effect of the availably of trade finance on trade flows differs across different country groups, above all with a view to different levels of income and levels of development. We find that import flows to non-OECD, lower and middle-income and developing countries are heavily supported by a higher flow of trade credit insurance. We also investigate the importance of trade finance across regions and find that trade finance is particularly important for sub-Saharan Africa.
Keywords: 330; Handel und Investitionen; Internationales Finanzsystem